Media portrayal of the illegal trade in wildlife: The case of turtles in the US and implications for conservation. Issue 2 (31st January 2023) - Easter, Tara; Trautmann, Julia; Gore, Meredith; Carter, Neil
Abstract: Illegal wildlife trade is a global threat to biodiversity, but its drivers and impacts and ways to combat it vary by taxa. News media framing of instances of illegal trade provides a novel window into understanding public perceptions of these dynamics and potential support for management actions. We used 54 known cases of illegal turtle trade in the United States occurring between 1998 and 2021 as a case study to investigate news media framing of this emergent issue in illegal wildlife trade. We synthesized information from these cases and qualitatively analysed how they were framed in 217 associated news articles. The 54 cases involved the illegal trade of at least 24, 000 freshwater turtles of 34 different species; box turtles ( Terrapene spp.) were traded the most. Of the known species involved, 23 were listed under one of the CITES Appendices, and 12 were considered threatened by the International Union for the Conservation of Nature. Trade occurred in at least 43 US states and 6 countries. Despite the multifaceted nature of these cases, problem and solution framing were relatively unvarying. Media coverage framed foreign demand, particularly from Asia for high‐value pet turtles, as a main driver of illegal trade. Solutions focused on regulations and enforcement which follows global trends in illegal wildlife trade discourses. However, we also found that articles neutralized illegal turtle trade in several ways, reflecting a lack of perceived legitimacy of and necessity for trade rules and enforcement. Without acknowledging longstanding and formerly legal practices in wildlife trading, conservation efforts which focus on regulations and enforcement may be undermined by a lack of normative compliance. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.